To simplify the expression \(- (2x + 6)(3x + 4) + 5x^2 - 7x\), we will follow these steps:
- Expand \(-(2x + 6)(3x + 4)\).
- Combine like terms.
Step 1: Expand \(-(2x + 6)(3x + 4)\)
First, we can expand \((2x + 6)(3x + 4)\):
\[ (2x + 6)(3x + 4) = 2x \cdot 3x + 2x \cdot 4 + 6 \cdot 3x + 6 \cdot 4 \] \[ = 6x^2 + 8x + 18x + 24 \] \[ = 6x^2 + 26x + 24 \]
Now, adding the negative sign in front:
\[ -(2x + 6)(3x + 4) = - (6x^2 + 26x + 24) = -6x^2 - 26x - 24 \]
Step 2: Combine with \(5x^2 - 7x\)
Now, we substitute this back into our original expression:
\[ -6x^2 - 26x - 24 + 5x^2 - 7x \]
Now combine the terms:
- Combine the \(x^2\) terms: \(-6x^2 + 5x^2 = -1x^2\)
- Combine the \(x\) terms: \(-26x - 7x = -33x\)
- The constant term is \(-24\).
Putting it all together, we get:
\[ -x^2 - 33x - 24 \]
So, the fully simplified expression is:
\[ -x^2 - 33x - 24 \]
The correct response is: \(-x^2 - 33x - 24\) (negative x squared minus 33 x minus 24).